Evaluation of Incorporating CKD and RAP on the Performance of Cohesive Soil - Saeed, Salman; Abdulkareem, Ahmed; Abd, Duraid (Iraqi Journal of Civil Engineering, 2022)
The aim of this study is to investigate the effect of adding recycled materials such as CKD and RAP to weak cohesive soils, in addition to evaluate the change in the strength of these soils. This study was conducted on soil type MH, and only RAP particles finer than 10 mm were used in preparing the mixtures. 7, 14, and 28 days were selected as curing periods for soil- CKD and soil- CKD- RAP mixtures to obtain the effect of curing periods on soil improvement. The results showed that adding 20% of CKD to the natural soil increased the unconfined compression strength UCS from 0.43 MPa to 2.6 MPa at a 28-day curing period. Also, the results showed that adding 25% of RAP to the soil- 20% CKD mixture increased the UCS value to 5.3 MPa after 28 days of the curing period. The final results showed that the optimum contents of CKD and RAP added to the cohesive soil were 20% and 25%, respectively, while the optimum curing period was 28 days